Technology "Feels Less Threatening": The processes by which digital technologies facilitate youths' access to services at intimate partner violence organizations. (August 2022) - Storer, Heather L.; Nyerges, Eva X.; Hamby, Sherry
Highlights: Digital technologies, such as chatlines or messaging on social media, hold promise for minimizing some of the known barriers to youths' service utilization at IPV organizations, including alleviating transportation and geographical barriers common among survivors living in rural communities. Leveraging youths' comfort and familiarity with technology can provide an entry point for more meaningful connection between service providers and youth survivors of abuse. Connecting virtually can be a starting point for building ongoing relationships. Service providers reported that youth still regard receiving services as stigmatized and threatening. While technology can address some of these issues, future research should explore ways to challenge and reduce stigma across the ecosystem, particularly at the community-level. Abstract: Youth survivors of teen dating violence (TDV) are hesitant to reach out for services from social service providers for fear of judgement and not being believed. Given the central role that technology plays in youths' lives, it has been suggested that digital innovations can help overcome some of these barriers. The present study explores the perceptions of service providers at Intimate Partner Violence (IPV) regarding ways in which technology can increase service access and utilization for youth. Using qualitative methodology, the interview sample includes thirty-five IPV service professionals in the United States. Analysis involved thematic content analysis methods that included multiple rounds of open and focused coding and the utilization of data matrices to facilitate within- and across-case analyses. The analysis yielded four primary thematic domains related to how technology facilitates youths' access to services: 1) youths' preference for and comfort with using digital modes of communication, 2) perceptions that digital forms of communication are less threatening and could thus function as an entry point for receiving services, 3) the potential for digital communication to help overcome the physical barriers to service access, and 4) youths' belief that digital modes of communication were more confidential. This study constructs knowledge regarding how technology might nurture youths' engagement with services at IPV organizations by functioning as a metaphorical bridge to service providers. Providers viewed digital communication as a tool to augment existing services rather than replace current in-person prevention or advocacy. While these findings provide evidence for the important role technology can play at GBV organizations, both providers and service users need to be cognizant of the limitations and biases associated with emerging technologies.